Analisis Eye-Tracking Pengalaman Pengguna pada TikTok Museum MACAN - Prameswari, Clarissa; Rahmi, Rahmi (Jurnal Sosioteknologi, 2024)
This experimental study explores how Generation Z and Y in Indonesia interact with Museum MACAN’s TikTok content, using eye-tracking to understand engagement with cultural content on this pivotal platform. Participants undertook tasks of varying lengths (120, 300, and 180 seconds) to reflect different engagement scenarios, with metrics like Participant Quality Grade (PQG), test duration, browser dimensions, K-factor, gaze, and fixation counts assessing interaction depth. Results indicate high engagement levels, with quality ranging from good to excellent and a noted preference for focal processing, suggesting users’ concentrated attention on video content. Heatmaps confirmed video content as the primary focus area. This study highlights TikTok’s role in enhancing museum engagement and provides insights for cultural institutions to refine their social media content strategies.